Protein aggregation model to explain the bioactivity of condensed tannins. (1st August 2023) - Yamauchi, Kosei; Soyano, Mayu; Kobayashi, Miho; Kamatari, Yuji O.; Mitsunaga, Tohru
Highlights: Structures of two condensed tannins were analyzed using thiolysis and HSQC NMR. Condensed tannin inhibited MMP-1 activity by the aggregation. The binding mode between the tannins and MMP-1 were elucidated by HSQC NMR. First 3D protein aggregation model of the condensed tannin and MMP-1 was presented. Abstract: Tannins are involved in the taste of foods and multi bioactivity of traditional herbal medicines. The characteristics of tannins are believed to derive from their connectivity with proteins. However, the mode of interaction between proteins and tannins is not yet understood because of the complexity of the tannin structure. Then this study aimed to elucidate the detail binding mode of tannin and protein by the 1 H- 15 N HSQC NMR method using the 15 N-labeled MMP-1that have not been used so far. The HSQC results suggested cross-link sites between MMP-1s, which cause protein aggregation and inhibit MMP-1 activity. This study presents the first 3D protein aggregation model of condensed tannins, which is important for understanding the bioactivity of polyphenols. Furthermore, it can broaden the understanding of the range of interactions between other proteins and polyphenols.